Developmental pathways from preschool irritability to multifinality in early adolescence: the role of diurnal cortisol. Issue 5 (20th April 2021) - Kessel, Ellen M.; Frost, Allison; Goldstein, Brandon L.; Black, Sarah R.; Dougherty, Lea R.; Carlson, Gabrielle A.; Klein, Daniel N.
Abstract: Background: Early irritability predicts a broad spectrum of psychopathology spanning both internalizing and externalizing disorders, rather than any particular disorder or group of disorders (i.e. multifinality). Very few studies, however, have examined the developmental mechanisms by which it leads to such phenotypically diverse outcomes. We examined whether variation in the diurnal pattern of cortisol moderates developmental pathways between preschool irritability and the subsequent emergence of internalizing and externalizing symptoms 9 years later. Method: When children were 3 years old, mothers were interviewed about children's irritability and completed questionnaires about their children's psychopathology. Six years later, children collected saliva samples at wake-up and bedtime on three consecutive days. Diurnal cortisol patterns were modeled as latent difference scores between evening and morning samples. When children were approximately 12 years old, mothers again completed questionnaires about their children's psychopathology. Results: Among children with higher levels of irritability at age 3, a steeper diurnal cortisol slope at age 9 predicted greater internalizing symptoms and irritability at age 12, whereas a blunted slope at age 9 predicted greater externalizing symptoms at age 12, adjusting for baseline and concurrent symptoms. Conclusion: Our results suggest that variation in stress system functioning can predict and differentiate developmental trajectories of early irritability that are relatively more internalizing v. those in which externalizing symptoms dominate in pre-adolescence.